Legal Framework and Failure to Create Free Economic Zones in Kosovo - KRASNIQI, Armand (Journal of Advanced Research in Law and Economics; Vol 8 No 1 (2017): JARLE Volume VIII Issue 1 (23) Spring 2017, 2017)
The Law on free economic zones exclusively regulates Establishment of free zones and free warehouses, their management and conducting economic activities. It is proven that the effects of these zones in countries in social – economic transition reflect positively in respect of incentives for the development of certain segments of economy, employment, and especially in the identity and reputation of the national economy. Even after five years of establishing a modest legal basis, in Kosovo not only any activity was undertaken for such zones, but it was not even thought or spoken about it. Public perception prevails that through such free zones country's economy might liberalize and favorable conditions for integration could be created. However, this legal framework should be supplemented with a series of legal acts of primary and secondary character detailing possible mitigations in the field of rule of customs, custom duties, tax mitigation and excise